1993
DOI: 10.1002/cne.903310402
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase neurons in the male hamster chemosensory pathway contain androgen receptors and are influenced by gonadal hormones

Abstract: Chemosensory and hormonal signals, both of which are essential for mating in the male Syrian hamster, are relayed through a distinct forebrain circuit. Immunocytochemistry for tyrosine hydroxylase, a catecholamine biosynthetic enzyme, previously revealed immunoreactive neurons in the anterior and posterior medial amygdaloid nucleus, one of the nuclei within this pathway. In addition, dopamine-immunoreactive neurons were located in the posterior, but not the anterior, medial amygdala. In the present study, tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 76 publications
4
21
0
Order By: Relevance
“…The chemical identity of these TH-immunoreactive (TH-ir) cells remains to be verified, but they do not contain dopamine ␤ -hydroxylase [Northcutt et al, 2007], so are not noradrenergic and may instead be dopaminergic (DAergic). Although a small number of TH-ir cells have been found in the Syrian hamster BST and MEA [Davis and Macrides, 1983;Vincent, 1988;Asmus et al, 1992;Asmus and Newman, 1993;Wommack and Delville, 2002;Northcutt et al, 2007], the very large populations of densely TH-ir cells found in male prairie voles do not exist in the BSTpr and MEApd of any other rodents examined to date [Albanese et al, 1986;Kalsbeek et al, 1992;Northcutt et al, 2007], which has led us to suggest that these cells may influence social behaviors relatively unique to prairie voles including high gregariousness, pair bonding and biparental care [Northcutt et al, 2007;Northcutt and Lonstein, 2009].…”
mentioning
confidence: 99%
“…The chemical identity of these TH-immunoreactive (TH-ir) cells remains to be verified, but they do not contain dopamine ␤ -hydroxylase [Northcutt et al, 2007], so are not noradrenergic and may instead be dopaminergic (DAergic). Although a small number of TH-ir cells have been found in the Syrian hamster BST and MEA [Davis and Macrides, 1983;Vincent, 1988;Asmus et al, 1992;Asmus and Newman, 1993;Wommack and Delville, 2002;Northcutt et al, 2007], the very large populations of densely TH-ir cells found in male prairie voles do not exist in the BSTpr and MEApd of any other rodents examined to date [Albanese et al, 1986;Kalsbeek et al, 1992;Northcutt et al, 2007], which has led us to suggest that these cells may influence social behaviors relatively unique to prairie voles including high gregariousness, pair bonding and biparental care [Northcutt et al, 2007;Northcutt and Lonstein, 2009].…”
mentioning
confidence: 99%
“…2( A)]. The rostro-caudal extent of this cell group was identical to that described previously in animals receiving colchicine (Asmus et al, 1992;Asmus and Newman, I993a). After immunostaining every section through this area, approximately 60 TH-immunoreactive neurons were observed in each brain from the three experimental groups.…”
Section: Co-localization Of Th and Fos In The Medial Amygdaloid Nucleusmentioning
confidence: 79%
“…Identification of many of the TH-immunostained neurons in Me requires pretreatment with colchicine (Asmus et al, 1992;Asmus and Newman, 1993a), an axoplasmic transport inhibitor (Dahlstrom, 1968). However, colchicine treatment has been reported to induce Fos in brain-stem catecholaminergic neurons (Ceccatelli et al, 1989) and, therefore, could not be used to examine the normal pattern of Fos immunostaining.…”
Section: Animals Behavioral Testing and Tissue Processingmentioning
confidence: 97%
See 2 more Smart Citations